2019
DOI: 10.1080/14737175.2020.1694409
|View full text |Cite
|
Sign up to set email alerts
|

Improving long term patient outcomes from deep brain stimulation for treatment-refractory obsessive-compulsive disorder

Abstract: Introduction: Deep brain stimulation (DBS) has emerged as an effective treatment for patients with severe treatment-refractory obsessive-compulsive disorder (OCD). Over the past two decades, several clinical trials with multiple years of follow-up have shown that DBS offers long-term symptom relief for individuals with severe OCD, though a portion of patients do not achieve an adequate response. Areas covered: This review sought to summarize the literature on the efficacy and long-term effectiveness of DBS for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 67 publications
(189 reference statements)
0
15
0
Order By: Relevance
“…An additional 19 of these were excluded due to the following reasons: not referring to CBT ( n = 11), not referring to DBS ( n = 1) and other reasons ( n = 7). Eventually, 9 papers were included in the review: three randomized controlled trials (RCTs) [ 13 , 14 , 15 ], one cohort study [ 16 ], one case series [ 12 ], one qualitative study [ 17 ], one systematic review [ 18 ] and 2 narrative reviews [ 19 , 20 ]. These reviews were focused on the efficacy of DBS for OCD and not on the efficacy of CBT after DBS for OCD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional 19 of these were excluded due to the following reasons: not referring to CBT ( n = 11), not referring to DBS ( n = 1) and other reasons ( n = 7). Eventually, 9 papers were included in the review: three randomized controlled trials (RCTs) [ 13 , 14 , 15 ], one cohort study [ 16 ], one case series [ 12 ], one qualitative study [ 17 ], one systematic review [ 18 ] and 2 narrative reviews [ 19 , 20 ]. These reviews were focused on the efficacy of DBS for OCD and not on the efficacy of CBT after DBS for OCD.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas it is a common practice to offer patients with therapy-resistant OCD treated with DBS a course of CBT after their operation, its effectiveness, timing and procedural aspects, such as the preferred way of delivery of such therapy, has hardly been studied. In spite of the fact that the importance of post-operative CBT is stressed by various authors [ 18 , 19 , 20 ], only two trials have specifically focussed on CBT added to DBS [ 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there are no established clinical predictors informing us which patients are most likely to respond to DBS (5). We rely mostly on illness severity, chronicity, and welldocumented evidence of treatment resistance to determine eligibility for DBS in adults with a primary diagnosis of OCD.…”
Section: The Main Limitation Of the Denys Et Al Study Is That The Majority Of Patients Received Dbs In An Open-label Fashionmentioning
confidence: 99%
“…This study adds to a growing body of evidence that DBS is generally safe and well tolerated for patients with intractable OCD (4,5). Adverse events were categorized as either related to surgery, the hardware, or programming.…”
mentioning
confidence: 99%
“…A recent literature review examining the long-term effectiveness of DBS for OCD in adults identified seven randomized shamcontrolled trials all of which demonstrated a lower mean Y-BOCS severity in the active compared to sham group. Moreover, this review found that "sixty-two percent of patients with treatmentrefractory OCD are estimated to experience clinically significant long-term treatment response from DBS" [10]. In light of these findings, DBS may one day be considered for use among pediatric populations.…”
Section: Introductionmentioning
confidence: 99%